Evaluation and synthesis of perovskite crystals as high-Z sensors for hybrid pixel detectors - R. B. Campanelli; G. S. Gomes; M. M. Donatti; L. S. Perissinotto; A. D. Pereira; E. B. Antonio; P. L. Vincoletto; M. G. Fernandes; L. S. Araujo; J. M. Polli; F. C. Marques (Scientific Reports)
Abstract High-energy photon imaging experiments are crucial techniques in synchrotron facilities, often employing hybrid pixel detectors for these operations. These detectors combine a photo-sensitive semiconductor component with a pixelated microelectronic Application Specific Integrated Circuit (ASIC) for signal processing and image formation. However, detecting photons above 90 keV poses significant challenges, even for heavy semiconductors, due to lower photoelectric absorption cross-section at this energy range. Nevertheless, lead-based perovskites, such as $${\text{CsPbBr}}_3$$ CsPbBr 3 , are remarkable alternatives as they present excellent cross-section values and noteworthy transport properties, contributing to increased high-energy detection efficiencies. Here, we employ a chemical synthesis route for $${\text{CsPbBr}}_3$$ CsPbBr 3 single-crystals, enabling experimental measurements of carrier mobility of 100.7 $${\text{cm}}^{2}$$ cm 2 /Vs. We also developed a simulation algorithm to calculate the current pulses generated on pixelated electrodes. Our simulations evaluate $${\text{CsPbBr}}_3$$ CsPbBr 3 ’s performance coupled with the latest photon-counter ASIC developed by CERN, the Timepix4. Our findings indicate that $${\text{CsPbBr}}_3$$ CsPbBr 3 crystals require intense applied electric fields, around 1 kV/mm, for accurate signal integration. Furthermore, we observed no correlation between incident energy and induced pulse width. Through microelectronics simulations, we demonstrate that the signal formation behavior of $${\text{CsPbBr}}_3$$ CsPbBr 3 is compatible with Timepix4 ASICs, consequently establishing operational guidelines for employing this promising material as sensors in hybrid pixel detectors.